The Development Dilemma in Contemporary Chile: A Historical-Structural Analysis. - Miguel Torres Olivos (Cuadernos de Economía)
This article examines the main aspects characterising the development process in contemporary Chile through a historical-structural analysis. In doing so, it identifies the current difficulties facing the country, framing them within a structural and cyclical context. Accordingly, it posits Chile’s problem as a misalignment between economic and social dynamics and the political sphere’s scope of action. To characterise this development dilemma, the article presents an analysis of the country’s political evolution over the last twenty years. The analysis is set within a broader historical framework spanning five decades examining the economic situation and social relations, drawing on ad-hoc historiographical sources and presenting a set of stylised facts that trace the principal trends in Chile’s development process.